Blood on their hands : how greedy companies, inept bureaucracy, and bad science killed thousands of hemophiliacs - Weinberg, Eric, 1955-; Shaw, Donna, 1951- (Rutgers University Press, 2017)
"A few short years after HIV first entered the world blood supply in the late 1970s and early 1980s, over half the hemophiliacs in the United States were infected with the virus. But this was far more than just an unforeseeable public health disaster. Negligent doctors, government regulators, and Big Pharma all had a hand in this devastating epidemic. Blood on Their Hands is an inspiring, firsthand account of the legal battles fought on behalf of hemophiliacs who were unwittingly infected with tainted blood. As part of the team behind the key class action litigation filed by the infected, young New Jersey lawyer Eric Weinberg was faced with a daunting task: to prove the negligence of a powerful, well-connected global industry worth billions. Weinberg and journalist Donna Shaw tell the dramatic story of how idealistic attorneys and their heroic, mortally-ill clients fought to achieve justice and prevent further infections. A stunning exposé of one of the American medical system's most shameful debacles, Blood on Their Hands is a rousing reminder that, through perseverance, the victims of corporate greed can sometimes achieve great victory."--Publisher's website